1994
DOI: 10.1042/bj3000263
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of fos-lacZ fusion gene expression in primary mouse epidermal keratinocytes isolated from transgenic mice

Abstract: The expression of a fos-lacZ fusion gene was studied in primary mouse epidermal keratinocytes obtained from transgenic mice. This gene construct contains the entire upstream regulatory sequence of c-fos, and expression of the endogenous and fusion gene was shown by Northern analysis to correlate upon induction with the phorbol ester 12-O-tetradecanoylphorbol 13-acetate (TPA). Using a chromogenic substrate of beta-galactosidase, we also demonstrated that expression of the fusion gene product, like that of Fos, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…The changes in PKD protein levels and serine 916 phosphorylation were measured at the time points of 8, 16, and 24 h because these time points encompass the rising phase (8 h), the maximal observed transglutaminase activity (16 h), and the plateau phase (24 h) after stimulation with 1 mM CaCl 2 (Fig 5). These time points also correspond to the previous report that elevated [Ca 2+ ] e (1 mM) treatment inhibits the proliferative response of keratinocytes as shown by the significant and maximal inhibition of DNA sythesis after 8 and 24‐h calcium treatments, respectively (Bollag et al , 1994). The data indicate that PKD protein levels and serine 916 phosphorylation were significantly downmodulated after 8, 16, and 24 h of elevated [Ca 2+ ] e treatment when compared with control (Fig 5).…”
supporting
confidence: 90%
“…The changes in PKD protein levels and serine 916 phosphorylation were measured at the time points of 8, 16, and 24 h because these time points encompass the rising phase (8 h), the maximal observed transglutaminase activity (16 h), and the plateau phase (24 h) after stimulation with 1 mM CaCl 2 (Fig 5). These time points also correspond to the previous report that elevated [Ca 2+ ] e (1 mM) treatment inhibits the proliferative response of keratinocytes as shown by the significant and maximal inhibition of DNA sythesis after 8 and 24‐h calcium treatments, respectively (Bollag et al , 1994). The data indicate that PKD protein levels and serine 916 phosphorylation were significantly downmodulated after 8, 16, and 24 h of elevated [Ca 2+ ] e treatment when compared with control (Fig 5).…”
supporting
confidence: 90%
“…Studies of the role of PKC in keratinocyte differentiation utilize phorbol esters [54,56,6973]. These compounds are capable of stimulating differentiation of keratinocytes at least in vitro even in low Cao conditions, although their effects can be potentiated by Cao [6973].…”
Section: Protein Kinase Cmentioning
confidence: 99%
“…As alluded to previously, activation of PKC leads to activation of transcription factors in the Fos/Jun families that probably mediate the effects of calcium, phorbol esters and DAG on keratinocyte differentiation [53,54,89–93]. These transcription factors bind to AP-1 sites in the regulatory regions of the genes that they regulate [94].…”
Section: Protein Kinase Cmentioning
confidence: 99%
“…We found that low concentrations of 1,25(OH),D3 (1 pM to 1 nM) actually stimulated cell growth, whereas at higher concentrations (10-1,000 nM) proliferation was inhibited, and we suggest that these may represent physiological and pharmacological effects of the hormone, respectively. We also investigated the ability of 1,25(OH),D3 to elicit rapid signal transduction events associated with keratinocyte differentiation-an elevation of intracellular calcium levels (Hennings et al, 1989;Sharpe et al, 1989;Pillai and Bikle, 1991) and expression of Fos (Fisher et al, 1991;Smeyne et al, 1992;Basset-Seguin et al, 1994;Bollag et al, 1994). We also determined the extent of growth inhibition after short exposures to the hormone.…”
Section: Incmentioning
confidence: 99%
“…After washing to remove the paraformaldehyde, the cells were solubilized with 0.5% Triton XlOO for 5 min a t room temperature. p-galactosidase activity was then measured essentially as described by MacGregor et al (1991), as detailed by Bollag et al (1994). Briefly, fixed cells were placed in Z buffer (60 mM Na,HPO,, 40 mM NaH,PO,, 10 mM KC1, and 1 mM MgSO,, pH 7.0) containing 0.1% Triton X100.…”
Section: Measurement Of P-galactosidase Activitymentioning
confidence: 99%